2012
DOI: 10.3892/ol.2012.558
|View full text |Cite
|
Sign up to set email alerts
|

The clinical value of CXCR4, HER2 and CD44 in human osteosarcoma: A pilot study

Abstract: Abstract. The biological markers CXCR4, HER2 and CD44 are involved in tumor growth and the homing of cancer cells to distant sites. The aim of this retrospective, case-control study was to evaluate whether the expression of CXCR4, HER2 and CD44 correlated with poor prognosis. Expression levels of CXCR4, HER2 and CD44 were evaluated by immunohistochemical staining in paraffin-embedded tissue sections of malignant primary osteosarcoma and related metastatic carcinoma from 63 patients, at a median follow-up of 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…It was found that the survival data of one article could not be used in this study. Finally, 6 [ 19 24 ] studies were included in this meta-analysis, which were published between1994 and 2014 (Figure 1 ). All of them were retrospective in design.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the survival data of one article could not be used in this study. Finally, 6 [ 19 24 ] studies were included in this meta-analysis, which were published between1994 and 2014 (Figure 1 ). All of them were retrospective in design.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we evaluated the expression of the following genes: ErbB2, TGFβ, CD44, IL6, IL10, IL15, IL8, CD14, NF-kB/p65 (p65), IL18, TLR4, TLR5, TP53, MD2, MyD88, STAT5, iNOS, CXCR4, RAD51 and PTEN [13][14][15][16][17][18][19][20][21][22][23][24][25]. Genes selection has been made on the basis of their pivotal role in immune response to bacteria (CD44, IL6, IL8, CD14, p65, IL18, TLR4, TLR5, MD2, MyD88, STAT5, iNOS,) [26] or OSA development and metastasis (ErbB2, TGFβ, CD44, TP53, MD2, MyD88, STAT5, CXCR4, RAD51, IL8, IL6 and PTEN) [27][28][29][30][31][32].…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…This will improve the chances for successful clinical development of a potential product, as it is often more difficult to fund a costly development program when the patient population is limited. The tumor-associated antigens HER2 and EGFR are both known to be expressed in OS [ 9 , 10 ]. Marketed immunotherapeutic antibodies targeting these antigens (trastuzumab and cetuximab) are successful for treatment of other cancers, and could be of relevance for targeted therapy of OS [ 11 ].…”
Section: Introductionmentioning
confidence: 99%